The ambivalence of gay liberation male homosexual politics in 1970s West Germany - Griffiths, Craig (Oxford University Press, 2021)
This text explores the different ways West Germans thought about and discussed being queer in the 1970s; a decade in the midst of the Cold War, sandwiched between the decriminalisation of homosexuality in 1969 and the HIV/AIDS crisis in the early 1980s.
Keywords: Geschichte 1970-1979; Male homosexuality -- Germany (West); Gay men -- Germany (West) -- Attitudes; Gay liberation movement -- Germany (West); Nineteen seventies; Mann; Homosexualität; Westdeutschland